Note—Controlling Inventories in an Acyclic Assembly System - Tang, Christopher S. (Management Science, 1992)
This note presents a model of an acyclic assembly system that faces yield loss and uncertain demand. While there is no known production rule for managing acyclic systems, we develop a production rule whose operating characteristics could be measured analytically. Thus, the operating characteristics can be used as a benchmark for future comparison. To facilitate our analysis, we extend the model for a serial production system that produces a single product (Tang 1990). This extension entails a modification of the production rule and the analysis of a decomposition scheme.